Writing and directing ADAM - Lin, Shoki Junxian (2019)
This FYP report is a thorough documentation of my creative and technical process in making the film “ADAM”. It touches upon the year long process from the pitching of the film to the festival strategy for our completed film. This report strives to give the reader an insight into the challenges of making a film and reveal the long drawn creative and technical process that it took to create out short film. This report also tells the process of the filmmaking process from not just my personal point of view as the writer and director of the film but also from a collective consideration of the team who have made this film possible.